2022
DOI: 10.1002/slct.202102954
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of 0D/2D WO3/g‐C3N4 Z‐scheme Hybrid for Improving Photocatalytic Dye Degradation

Abstract: A Zero-dimensional/two-dimensional (0D/2D) tungsten trioxide/graphitic carbon nitride (WO 3 /g-C 3 N 4 ) Z-scheme hybrid was prepared by employing a simple calcination process. Then, the photocatalytic property of the WO 3 /g-C 3 N 4 hybrids was assessed through their efficiency in the degradation of toxic industrial dye pollutant, Rhodamine B (RhB) and phenol under visible light irradiation. From the results and analysis, the 1 % WO 3 /g-C 3 N 4 composite with a larger Brunauer-Emmett-Teller (BET) surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Therefore, it is commonly adopted to form Z-scheme heterojunctions with semiconductors which have low valance band maximum (VBM). Previous studies have confirmed that WO 3 is an appropriate semiconductor to construct Z-scheme heterojunction with g-C 3 N 4 , which exhibits well-matched band structure [6][7][8][9][10][11][12]. Currently most WO 3 /g-C 3 N 4 heterojunctions reported are based on twodimensional (2D) g-C 3 N 4 nanosheets [13,14], and there are few researches focusing on one-dimensional (1D) g-C 3 N 4 nanotubes which actually show good photocatalytic activity.…”
Section: Introductionmentioning
confidence: 86%
“…Therefore, it is commonly adopted to form Z-scheme heterojunctions with semiconductors which have low valance band maximum (VBM). Previous studies have confirmed that WO 3 is an appropriate semiconductor to construct Z-scheme heterojunction with g-C 3 N 4 , which exhibits well-matched band structure [6][7][8][9][10][11][12]. Currently most WO 3 /g-C 3 N 4 heterojunctions reported are based on twodimensional (2D) g-C 3 N 4 nanosheets [13,14], and there are few researches focusing on one-dimensional (1D) g-C 3 N 4 nanotubes which actually show good photocatalytic activity.…”
Section: Introductionmentioning
confidence: 86%
“…Other than the recombination with UV-active TiO 2 and ZnO semiconductor, WO 3 has received prodigious attention as a promising candidate owing to its relatively lower band gap (2.5–2.8 eV), which lies in the visible-light range, thus increasing the potential for wider utilize in the PEC applications [ 192 , 193 , 194 ].…”
Section: Composite Films Of G−cn As Highly Valid Photoelectrodes For ...mentioning
confidence: 99%